2.3 GPa cryogenic strength through thermal-induced and deformation-induced body-centered cubic martensite in a novel ferrous medium entropy alloy. (November 2021) - Kwon, Hyeonseok; Sathiyamoorthi, Praveen; Karthik, Gangaraju Manogna; Asghari-Rad, Peyman; Zargaran, Alireza; Do, Hyeon-Seok; Lee, Byeong-Joo; Kato, Hidemi; Kim, Hyoung Seop
Abstract: A novel non-equiatomic FeCoNiAlTiMo ferrous medium-entropy alloy (MEA) with ultra-high tensile strengths at 298 and 77 K is presented in this work. By subjecting the MEA to hot rolling without further heat treatment, a quasi-dual-phase microstructure consisting of retained face-centered cubic (FCC) and thermal body-centered cubic martensite (BCC) phases with a very high density of dislocations and precipitates of Mo-rich µ phase was created. The high dislocation density significantly accelerated deformation-induced martensitic transformation from the remaining metastable FCC to BCC and successfully increased strain hardening ability. The strain hardening ability was even higher at 77 K due to decreasing FCC phase stability at lower temperatures. The increased strain hardening ability led to an excellent balance of strength and ductility, with ultimate tensile strength/uniform elongation of 1.5 GPa/ 15% at 298 K and 2.3 GPa/ 11% at 77 K. Graphical abstract: Image, graphical abstract